“Alchemizing Sorrow Into Deep Determination”: Emotional Reflexivity and Climate Change Engagement - Hamilton, Jo (Frontiers in Climate, 2022)
There are a range of emotions and affects related to climate change, which are experienced by different publics at different times. These include grief, fear, hopelessness, guilt, anxiety and anger. When unacknowledged or unprocessed, these emotions and affects can contribute to emotional paralysis and systems of socially organised denial, which can inhibit climate change engagement at individual and collective scales. Emotional reflexivity describes an awareness of the ways that people engage with and feel about issues, how this influences the actions they take, the stories they inhabit and their perceptions of possible change. How practices of emotional reflexivity relate to people becoming and remaining engaged with climate change has been identified as a research gap. Emotional reflexivity could be developed through approaches that incorporate psychological and social engagements with climate change. This article presents a summary of research conducted in the UK during 2018-2020 with participants of two such approaches: the ‘Work That Reconnects’ and the ‘Carbon Literacy Project’. I demonstrate how emotional reflexivity was developed through: 1. Awareness and acknowledgement of emotions, which helped to facilitate feedback between the dimensions of engagement and contributed to becoming engaged with climate change, and 2. Expression and movement of emotions, which enabled a changed relationship to, or transformation of emotions, which contributed to a more balanced and sustained engagement. A key finding was the relationship between ongoing practices of emotional reflexivity and engaging and sustaining engagement with climate change. Without ongoing practices, my research evidenced forms of defensive coping, ambivalence and vacillation, which impeded active engagement. These findings attest to the importance of attention to the dynamics and movement of emotions and affects relating to climate change. The approaches helped to cultivate forms of emotional reflexivity which contributed to a ‘deep determination’ and ongoing resource to act for environmental and social justice, and to live the future worth fighting for in the present.